ROBUST CONTROLLER IMPLEMENTATION VIA STATE-DERIVATIVE FEEDBACK IN AN ACTIVE SUSPENSION SYSTEM SUBJECTED TO FAULT - Pires da Silva, Emerson Ravazzi; Assuncao, Edvaldo [UNESP]; Minhoto Teixeira, Marcelo C. [UNESP]; Cardim, Rodrigo [UNESP]; IEEE (Ieee, 2013)
This work is focused on a practical implementation, of a robust controller designed by LMIs (Linear matrix inequalities), in an active suspension system manufactured by the Quanser (R). For the implementation, it is supposed that the active suspension system is subject to an uncertainty in the model and fault in the actuator. While most works found in literature use state feedback for the control design, this work considers the state-derivative feedback. The motivation for the use of state-derivative feedback is due to its easy implementation in some mechanical applications, for example, in vibration control of mechanical systems, where accelerometers have been used to measure the system state. The results show a good performance of the control theory applied to the active suspension physical model.
Keywords: State-derivative feedback; robust control; active suspension system with uncertainty; actuator fault; practical implementation